Western Interventionism and its Impacts on Global Peace and Security: A critical Examination of Foreign Policy Decisions - Muhammad Zohaib Mazhar; Fahad Ali (`, 2025)
Western interventionism, that's described as army, monetary, or political meddling within the inner affairs of other international locations, has had an extensive impact on global peace and safety and has produced complex and regularly contradictory outcomes. These overseas coverage alternatives, which might be motivated via geopolitical, economic, humanitarian, and counterterrorism dreams, have every so often resulted ultimately of atrocities and the elimination of repressive governments, as is the case in several regions of the Balkans. Critics counter that these interventions often boom instability, extend wars, bring about large-scale civilian losses, and engender strong anti-Western sentiment. Unintentional effects, including the emergence of extremist companies and ongoing disorder, have regularly been caused by incomplete post-intervention making plans, misguided intelligence, and a loss of consideration for neighborhood settings. to be able to honestly improve international balance, a essential evaluation in the long run highlights the necessity of a more complicated, multilateral, and context-aware approach to worldwide participation, shifting away from unilateral impositions and towards lengthy-term, regionally-driven peace building tasks. Keywords: Western Interventionism, Global Security, Foreign Policy, Conflict Dynamics, State Sovereignty, Humanitarian Intervention, Unintended Consequences, International Law